2017
DOI: 10.24071/llt.v19i1.311
|View full text |Cite
|
Sign up to set email alerts
|

Code Switching in the Instructions of English Language Education Study Program Lecturers

Abstract: Language is an essential mean of communication in teaching and learning activities. Specifically, in the English Language Education Study Program (ELESP) that employs English as the main instructional language for teaching and learning activities. Considering that English was not students first language, some lecturers employed code switching to help third-semester students in learning English. With regard to this phenomenon, this study addressed two research questions. First, what the types of code switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…For the discussion of the items in the affective domain, we can conclude that they have a fairly high value where the respondents mostly agree that English-Indonesian code-mixing can attract their attention and also, they feel confident towards it. Code-switching in a study by Mukti and Muljani (2016) shows that students are more interested and pay attention to teachers when explaining lessons in class when the teachers perform the code-mixing. Then, code-mixing in a study by Leung (2010) about code-mixing in advertisements found that codemixing alone can attract the attention of readers and listeners, let alone the audience who has a higher educational background.…”
Section: Discussionmentioning
confidence: 99%
“…For the discussion of the items in the affective domain, we can conclude that they have a fairly high value where the respondents mostly agree that English-Indonesian code-mixing can attract their attention and also, they feel confident towards it. Code-switching in a study by Mukti and Muljani (2016) shows that students are more interested and pay attention to teachers when explaining lessons in class when the teachers perform the code-mixing. Then, code-mixing in a study by Leung (2010) about code-mixing in advertisements found that codemixing alone can attract the attention of readers and listeners, let alone the audience who has a higher educational background.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on phenomenon of code switching from various languages, object and research prespectives have been widely published. Some previous studies such as done by Sari et al (2021), Rahmaniah (2016), Mukti & Muljani (2016), Cakrawati (2011), Riyanto (2010. But studies in analyzing code switching by taking YouTube videos, namely vlogs as data sources are still rarely found.…”
Section: Introductionmentioning
confidence: 93%
“…The use of code-switching in the EFL classroom as strategy has interested researchers to analyzed it in sociolinguistics field (Malik, 2014;Modupeola, 2013;Wang, 2017;Weng, 2012) function that was used by teachers when they practice code-switching (Azlan & Narasuman, 2013;Johansson, 2013;Ramasari & Kumalasari, 2018;Tajudin, 2013;Zulfa, 2016). Besides the function of code-switching, researchers also wants to find out the types of code-switch that was used in the class (Hutahuruk, 2016;Mukti & Muljani, 2016).The use of code-switching in the EFL classroom is inseparable from the teacher as classroom facilitator in EFL class. The teacher believes in conducting the code-switch also interest researcher (Bensen & Çavuşoğlu, 2013;Engku Ibrahim et al, 2013) and also students perception of the use in EFL Classroom (Fuente, 2021) Nevertheless, there are still many issues to investigates when the code-switching is conducted in EFL classroom.…”
Section: Introductionmentioning
confidence: 99%